Implementation of the Assure Model Using Google Site Media in Learning Procedure Texts - Dhita Nur Fitriana; Hartono (Britain International for Academic Research (BIAR) Publisher, 2023)
Education in Indonesia is of low quality. Learning media is one component that can be used as an effort to improve the quality of education in Indonesia. Teachers as learning facilitators have a role in determining appropriate learning media for student characteristics so that learning outcomes and student interest in learning increase. The lack of varied learning makes students more lazy in studying, especially studying Indonesian. Based on the results of observations at SMP Negeri 21 Semarang, the problem was found that the boredom experienced by students in learning was due to the learning media presented by the teacher needing to be more varied and innovative. Based on the problems found, the research intended to determine the implementation of the ASSURE learning model using Google Site media in learning procedure texts. The research was conducted in class VII A of SMP Negeri 21 Semarang. The number of research subjects was 33 students, 15 men and 18 women. The research was carried out in November in semester 1 of the 2022/2023 academic year. Data collection was carried out by observation or observation and interviews. Data analysis was carried out using three steps: data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the ASSURE model using Google Site media in learning procedural texts went well. Through the use of learning media that is different from usual, students are interested in learning so that learning activities do not feel boring and the learning outcomes are also in accordance with the learning objectives.